Post-Arab Spring Tunisia: Socio-Political Dynamics and Institutional Reform in a Post-Revolution Era - Zayyan Malik Fawwaz; Awangku Hafiz Awang Junaidi; Jessica Clarke; James Anderson; Raihan Zulkarnain Amir (Senarai: Journal of Islamic Heritage and Civilization, 2025)
This article explores Tunisia’s transformation a decade after the Arab Spring in the social, political, legal, and educational fields. The methods used include qualitative descriptive analysis and social history. Data was collected through heuristic methods, utilizing online sources about Tunisia, such as scientific articles, journalistic reports, dissertations, and reports from international institutions. This article demonstrates that the transformation in Tunisia’s socio-political, legal, and educational sectors is not only dynamic, reflecting the principles of a modern and democratic state, but also indicates a tendency to strengthen the stability of both the government and the state. Tunisia implemented new constitutional reforms in 2022 and transformed the education sector by improving both the quality and infrastructure of education. Based on these find- ings, the article concludes that a country’s transformation, including that of Tunisia, is determined by the dynamics of its socio-cultural, political, legal, and educational structures.